2022
DOI: 10.3390/w14040625
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Evaluation of the Influences of Precipitation and River Level Fluctuations on Groundwater in Yoshino River Basin, Japan

Abstract: Precise evaluation of the correlations among precipitation, groundwater and river water enhance our understanding on regional hydrological circulation and water resource management. The innovative and efficient use of wavelet analysis has been able to identify significant interactions in the spatial and temporal domains and to estimate the recharge travel time. In this paper, a wavelet analysis was utilized to analyse 43 years of monthly, and 2 years of daily, precipitation, river level and groundwater level d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The results showed that the lag response time of karst water level was 110-165 days to precipitation and 105-162 days to the Yellow River stage. Through the wavelet analysis conducted by Dong et al [32], it was found that the delayed response times of groundwater level to precipitation and river stage were 4-128 days and about 1 year, respectively, in the Yoshino River basin, Japan during 1972-2014 and the lag response times varied significantly with seasons.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the lag response time of karst water level was 110-165 days to precipitation and 105-162 days to the Yellow River stage. Through the wavelet analysis conducted by Dong et al [32], it was found that the delayed response times of groundwater level to precipitation and river stage were 4-128 days and about 1 year, respectively, in the Yoshino River basin, Japan during 1972-2014 and the lag response times varied significantly with seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Coupling the calculation of the standardized precipitation index (SPI; [237]) with the standardized groundwater level index (SGI; [238,239]) can be used to relate precipitation to groundwater recharge [240,241]. These metrics affect FRE riparian productivity [242,243] (e.g., [244][245][246][247][248]) through groundwater recharge in relation to river stage [249], and are affected by air temperature [250][251][252] and extreme precipitation events [253][254][255], which in turn affect stream discharge [256], groundwater recharge and availability [257,258], and phreatic zone and riparian rooting depth [259]. Inorganic sediment transport and turbidity generally (but not always) increase with stream order, reducing downstream PAR availability and 1° through 3° aquatic production [81] and strongly influencing aquatic macroinvertebrate feeding guild structure [6] and riparian nutrient availability.…”
Section: (A) Expanded Detail Of Foodweb Linkages In Fres Contrasting ...mentioning
confidence: 99%
“…However, it will need to consider more complicated models and factors in the future study [41]. Finally, many researchers have recently studied the relationship between groundwater and rainfall based on wavelet analysis [42,43] and time series analysis [44,45]. Dong et al (2022) used methods based on a wavelet technique to investigate the coherence and phase lag between precipitation, river levels, and groundwater [42].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, many researchers have recently studied the relationship between groundwater and rainfall based on wavelet analysis [42,43] and time series analysis [44,45]. Dong et al (2022) used methods based on a wavelet technique to investigate the coherence and phase lag between precipitation, river levels, and groundwater [42]. Gu et al (2022) used partial wavelet coherency (PWC) to evaluate the bivariate relationships between GWL and precipitation or surface water.…”
Section: Introductionmentioning
confidence: 99%